Ambient Intelligence in Automated Houses - El-Abd, Mohammed (2017)
Smart houses are invading nearly all modern companies under the flag of the booming field of home automation. This field is being implemented with the highest technologies to be integrated in daily life and be a non-neglect able part of everyone's life style. This field is growing at a fast pace as the field of smart devices was years ago. The main purpose of smart houses and home automation is to provide a more luxurious lifestyle to its users. However, throughout the span of the past years, there was not as much attention paid to the possibility of dangerous situations as the attention paid to providing luxurious welfare. The proposed home automation system in this work provides both luxurious and emergency features. There are six features discussed throughout this paper that shows how a house can deal with home tenant and the surrounding environment in case of emergency or dangerous situation.